Analisis Kestabilan Lereng Dengan Metode Slope Mass Rating (SMR) pada Jalan Alternatif Tenggarong, Kelurahan Lok Bahu, Kecamatan Sungai Kunjang, Kota Samarinda, Provinsi Kalimantan Timur - Muhammad Arif Faturrahman; Muhammad Amin Syam; Puspa Indah Rindawati (Mataram University, 2026)
This study aims to analyze rock slope stability based on the Slope Mass Rating (SMR) value at the research area located on the Tenggarong Alternative Road, Lok Bahu Village, Sungai Kunjang District, Samarinda City, East Kalimantan Province. The SMR method is a development of the Rock Mass Rating (RMR) rock mass classification system combined with correction factors related to the orientation of discontinuity planes relative to the slope direction. The parameters used in this study include rock compressive strength obtained from the Point Load Index (PLI) test, Rock Quality Designation (RQD) values calculated using the scanline method, joint spacing, joint condition, and groundwater condition. The analysis results indicate that the slope-forming lithology is dominated by sandstone with an RMR value of 63, which falls into class II (good). Kinematic analysis using stereonet shows the potential for wedge failure caused by the intersection of two discontinuity planes with a probability of occurrence of 15.97%. Based on the correction of discontinuity orientation relative to the slope, the SMR value obtained is 54, which is classified as class III (normal). This indicates that the slope condition is generally fairly stable but still has the potential for failure, particularly wedge failure; therefore, periodic monitoring and slope management are required to minimize the risk of landslides in the study area.